Does the Neighborhood Context Shape Violent Victimization Independent of Delinquency? A Mediation Analysis of Victimization among German Urban Adolescents. Issue 2 (17th February 2021) - Erdmann, Anke
ABSTRACT: Research findings suggest that there is a strong relationship between offending and being a victim of crime, whereby victimization is often a consequence of delinquent behavior. Therefore, impacts of explanatory variables on victimization might only occur as a noncausal by-product induced by their influences on delinquency. This study investigates the influences of neighborhood characteristics on violent victimization while also considering the role of delinquency as a potential mediator. Using a sample of 3, 065 15-year-old students from a long-term study on crime conducted in Germany, structural equation modeling is applied to examine the influence of neighborhood characteristics on offending and victimization. Additionally, influences on victimization are decomposed into direct and indirect effects to examine mediation via delinquency. The results show that – when analyzing offending and victimization simultaneously – influences on victimization are actually mediated through delinquency. Neighborhood context (disorder, leisure opportunities, perceived safety) mainly shapes offending. This investigation cannot provide evidence for direct influences of neighborhood characteristics on victimization that are independent of a person's delinquent behavior. Effects on violent victimization emerge from mediation via delinquency, particularly violent offending. These findings help to further disentangle impacts on victimization risk and point out implications for crime and victimization prevention within neighborhoods and cities.